The interaction between DNA methylation and long non‐coding RNA during the onset of puberty in goats. (7th July 2018) - Yang, Chen; Gao, Xiaoxiao; Ye, Jing; Ding, Jianping; Liu, Ya; Liu, Hongyu; Li, Xiumei; Zhang, Yunhai; Zhou, Jie; Huang, Weiping; Fang, Fugui; Ling, Yinghui
Contents: Epigenetics plays an important role in controlling female puberty. Both DNA methylation and long non‐coding RNAs (lncRNA) regulate the initiation of puberty by affecting the expression of genes related to puberty. While recent studies have indicated that DNA methylation of lncRNA represses the expression of lncRNA, its role in regulating puberty remains unclear. To explore the mechanism between DNA methylation and lncRNAs during puberty onset, we performed whole‐genome bisulphite sequencing (WGBS) and RNA‐sequencing (RNA‐seq). We found that DNA methylation was inversely correlated to gene expression levels during puberty. Methylation levels gradually decreased near the transcription initiation site and were present at high levels in the exon, intron and 3′ untranslated regions. In the promoter, lncRNA expression was negatively related to DNA methylation. We reported hypermethylation in the gene body and downstream of the lncRNA compared with upstream regions. In GO and KEGG analyses, we found enriched target genes of lncRNA, XLOC_960044 and XLOC_767346. During puberty, methylation of these genes increased while expression decreased. Our study indicates that DNA methylation of the promoter is negatively correlated with lncRNA during puberty onset, and methylation regulates the initiation of puberty via lncRNA, which provides new insight into the epigenetic mechanism of puberty onset.